Processing Tomato Powder (Licopersicon esculentum Mill.) By â€œFoam-Mat Dryingâ€ - Kamsiati, Elmi (Jurnal Teknologi Pertanian, 2006)
The aim of the research on processing of tomato powder (Licopersicon esculentum Mill.) by means of â€foam-mat dryingâ€ were to investigate the effect of foaming agents on physical-chemical characteristics of tomato powder. Egg white (0; 2; 5 % b/b) combined with Tween 80 ( 0; 0,2; 0,5 % b/b) was used as the foaming agents. The results showed that the increase of egg white concentration very significantly increased the levels of vitamin C, pH, yield and water vapor reabsorbs ion, but reducedÂ Â  the titratable acidity. Whereas the increase of Tween 80 concentration very significantlyÂ  increased the vitamin C content, water vapor re-absorbsionÂ  and the dispersion stability. The tomato powder with best characteristics was produced by the use of egg white only (2%) as the foaming agent. The yield obtained was 17.8% and contained 2.22% moisture, 68.05% total sugar, 5.50% titratable acidity, pH 3.75 and vitamin C of 77,77 mg. 10-2 g-1. The respective water vapour reabsorbsion and dispersion stability of the product were 2.72% and 83.22%. Â  Key words: tomato powder, foam-mat drying,Â  foaming agent